The Effectiveness of Cognitive Behavioral Therapy on Rumination, and Quality of Life among Girls with Body Dysmorphic Symptoms - Hashemi Salehi, Mir Mehdi; Aleyasin, Seyed Ali (Health Nexus, 2024)
The objective of this study was to evaluate the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing rumination and enhancing quality of life among girls diagnosed with Body Dysmorphic Disorder (BDD). This randomized controlled trial involved 60 participants, diagnosed with BDD, who were recruited from the Pouyesh Clinic in Tehran in 2023. Participants were randomly assigned to either a CBT intervention group or a control group, with each group comprising 30 participants. The intervention consisted of ten 75-minute sessions of CBT specifically tailored to address rumination and improve quality of life. Data were collected at baseline, immediately post-intervention, and at a three-month follow-up, and analyzed using Analysis of Variance with Repeated Measurements and Bonferroni post-hoc tests. The CBT intervention led to a significant reduction in rumination, with mean scores decreasing from 18.45 (SD = 3.52) pre-treatment to 13.67 (SD = 3.01) post-treatment, and slightly rising to 14.22 (SD = 2.86) at follow-up. Quality of life significantly improved, increasing from a mean of 42.58 (SD = 4.45) pre-treatment to 49.73 (SD = 4.12) post-treatment, with a slight reduction at follow-up to 48.89 (SD = 3.98). Statistical analysis confirmed significant time effects (F(2, 116) = 19.45, p < 0.001, η² = 0.15) and time × group interaction effects (F(2, 116) = 11.58, p < 0.001, η² = 0.10). The findings suggest that CBT is effective in significantly reducing rumination and improving quality of life among girls with BDD. The intervention showed durability of effects at a three-month follow-up, indicating its potential for long-term benefits. These results support the incorporation of CBT into treatment protocols for BDD to address specific cognitive processes and enhance overall well-being.